Organizational Structure and Its Influence on Decision-Making: A Bibliometric Analysis - Varjão dos Santos, Ainara Alícia; de Souza Filho, Theophilo Alves; de Sá Medeiros, Haroldo; Passos da Silva, Rosália Maria (International Journal for Innovation Education and Research, 2020)
This research aimed, through a bibliometric analysis, to generate a Bibliographic Portfolio of articles submitted for aligning organizational matters and taking public administration. National and international literature was used in order to contribute and facilitate the investigation of future research on the related theme. For the analysis, the Proknow-C methodology was used, with a publication time limit of 20 years, from 1999 to 2019, using Scopus, Web of Science and Spell as databases. A research resulted in the construction of a portfolio containing 4 research articles that shown alignment with the topic. Two articles aimed to build models to optimize management decision making in the complex environment of applicable technologies and resources, while the other articles analyze the decision making process, one article related to structured ethical decision and the other to public participation in decision making in four different countries. The content of the Bibliographic Portfolio allows a direction for future research, allowing the development of theoretical bases on the articles that stood out in the research.